ESTABLISHMENT OF THE FIRST RUSSIAN CONSULATES IN CHINA IN 1851–1852 - E. P. Koudryavtseva (Vestnik MGIMO-Universiteta, 2018)
The First Russian consulates in Western China were established in 1851. Russian representatives I. Zakharov and A. Tatarinov arrived in Kulja and Chuguchak in early 1852. Numerous reports of the Russian consuls to the Asian Department of the Russian Ministry of Foreign Affairs contain highly interesting material concerning the first diplomatic contacts between Russia and China. None of the documents from the Archive of the Russian Ministry of Foreign Affairs were used by national historians, they only mentioned the fact, that according to the Treaty of Kulja Chinese cities Yili and Tarbagatai hosted Russian representatives that looked after trade. Documents from the Archive of the Russian Ministry of Foreign Affairs reveal how the first Russian consuls arranged Russian factories in Xinjiang, how they interacted with local authorities and traders, course of barter. Establishment of the first Russian consulates was essential for the further development of diplomatic relations: in 1858 China opened 7 seaports for Russian traders, in 1861 the first Russian diplomatic representative was appointed to China. Isolationism that China adhered to was left behind to promote fullscale diplomatic relations. Russian consulates were the first diplomatic missions in the Qing China and played a big role in the development of the Russian-Chinese relations.